Differences in Responses of Immunosuppressed Kidney Transplant Patients to Moderna mRNA-1273 versus Pfizer-BioNTech - Dulat Bekbolsynov; Andrew Waack; Camryn Buskey; Shalmali Bhadkamkar; Keegan Rengel; Winnifer Petersen; Mary Lee Brown; Tanaya Sparkle; Dinkar Kaw; Fayeq Jeelani Syed; Saurabh Chattopadhyay; Ritu Chakravarti; et al. (Vaccines, 2024)
Immunosuppressed kidney transplant (KT) recipients produce a weaker response to COVID-19 vaccination than immunocompetent individuals. We tested antiviral IgG response in 99 KT recipients and 66 healthy volunteers who were vaccinated with mRNA-1273 Moderna or BNT162b2 Pfizer-BioNTech vaccines. A subgroup of participants had their peripheral blood leukocytes (PBLs) evaluated for the frequency of T helper 1 (Th1) cells producing IL-2, IFN-γ and/or TNF-α, and IL-10-producing T-regulatory 1 (Tr) cells. Among KT recipients, 45.8% had anti-SARS-CoV-2 IgG compared to 74.1% of healthy volunteers (p = 0.009); also, anti-viral IgG levels were lower in recipients than in volunteers (p = 0.001). In terms of non-responders (≤2000 U/mL IgG), Moderna’s group had 10.8% and Pfizer-BioNTech’s group had 34.3% of non-responders at 6 months (p = 0.023); similarly, 15.7% and 31.3% were non-responders in Moderna and Pfizer-BioNTech groups at 12 months, respectively (p = 0.067). There were no non-responders among controls. Healthy volunteers had higher Th1 levels than KT recipients, while Moderna produced a higher Th1 response than Pfizer-BioNTech. In contrast, the Pfizer-BioNTech vaccine induced a higher Tr1 response than the Moderna vaccine (p < 0.05); overall, IgG levels correlated with Th1(fTTNF-α)/Tr1(fTIL-10) ratios. We propose that the higher number of non-responders in the Pfizer-BioNTech group than the Moderna group was caused by a more potent activity of regulatory Tr1 cells in KT recipients vaccinated with the Pfizer-BioNTech vaccine.